Manufacturing system architecture for cost-effective mass-individualization. (April 2018) - Gu, Xi; Koren, Yoram
Abstract: Globalization and social networks are dramatically changing the producer-buyer landscape. Consumers have an increasing desire to buy unique products that precisely reflect their individual preferences and needs. Therefore, approaching the era of mass-individualization in which Market-of-One products are manufactured economically is inevitable. This emerging paradigm brings engineering challenges in designing new manufacturing systems that produce large quantities of individualized products at relatively low cost. We propose a new manufacturing system architecture that satisfies the production requirement for the mass-individualization paradigm. In the proposed system, individualized products can be manufactured cost-effectively, making them affordable for the general public. Operational challenges of the proposed system are highlighted.